Glucocorticoid and mineralocorticoid receptor polymorphisms and recurrence of major depressive disorder. (May 2015) - Hardeveld, Florian; Spijker, Jan; Peyrot, Wouter J.; de Graaf, Ron; Hendriks, Sanne M.; Nolen, Willem A.; Penninx, Brenda W.J.H.; Beekman, Aartjan T.F.
Highlights: We studied whether GR and MR polymorphisms were related to depression recurrence. GR or MR polymorphisms were not associated with recurrence of depression. No interaction effects with stressful conditions were found. Summary: Objective: Previous research found that variants of the glucocorticoid receptor (GR) (9β, ER22/23EK, Bcl I, TthIII l, NR3C1-1 and N363S) and mineralocorticoid receptor (MR) gene polymorphism (−2 C/G and I180V) are associated with both glucocorticoid (GC) sensitivity and major depressive disorder (MDD). There are no data which investigated prospectively whether these variants are associated with recurrence of MDD. Methods: Data were derived from the Netherlands Study of Depression and Anxiety (NESDA) which used the Composite International Diagnostic Interview (CIDI) to determine MDD. Polymorphisms in the GR and MR gene were determined and haplotypes were characterized. We analyzed in retrospect whether recurrent MDD ( n  = 951) in comparison with first onset MDD ( n  = 919) was associated with polymorphisms in the GR and MR gene. Furthermore, we analyzed prospectively for 4 years the time to recurrence among 683 subjects with a remitted MDD diagnosis. Time to recurrence of MDD was assessed using the CIDI and a life chart interview. Additionally, we analyzed interactions of the investigated polymorphisms with childhood trauma and recent negative life events. Results: GR and MR gene polymorphisms and derived haplotypes were not associated with recurrence of depression in both retrospective and prospective analyses. In addition, no consistent interactions between GR and MR polymorphisms and childhood trauma or life events were found. Conclusion: This study did not find consistent associations between GR and MR gene polymorphisms, interactions between GR and MR haplotypes and stressful conditions and recurrence of MDD.